Social media in agricultural extension and marketing - Rohila, Anil Kumar; Kumar, Ajay (Indian Farming, 2019)
Social media can play an important role in disseminating the timely and required agricultural information to the farmers. It has become a powerful tool that connects millions of people globally from the comfort of our homes and now-a-days it continues to grow in popularity with the increase in the number of smart phones, and the ease of use. The social media is sharing information and creating awareness among farming communities, about agricultural practices research, innovative work done in laboratories which is brought to land through agricultural extension personnel. Social media runs through Facebook, Twitter, YouTube, WhatsAspp, Linkedln, Skype etc.